Visual strategies for preventing iodine deficiency disorders in rural Indonesia: Poster-based health education for housewives - Bujawati, Emmi; Handayani, Nurul Ridhia Putri; Azis, Erina Widiyanti; Nasaruddin, Qonitah (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2025)
Iodine deficiency disorders (IDD) remain a significant public health challenge in Indonesia, particularly in rural areas where access to health information is limited. Despite various interventions, there is a lack of sustained and accessible educational strategies tailored to rural communities. This study aimed to evaluate the effectiveness of door-to-door education using poster-based media in increasing housewives’ knowledge about iodized salt consumption in Tokka Hamlet, Rumbia District, Jeneponto Regency. A pre-test and post-test study design was implemented, with three assessment points: before the intervention, immediately after, and six months post-intervention. A total of 30 participants received the educational intervention accompanied by visual poster materials. Knowledge scores were analyzed using the Friedman test to determine significant changes over time. Results revealed an initial increase in median knowledge scores from 47.00 (pre-test) to 86.00 (post-test I), followed by a decline to 57.00 at post-test II. The Friedman test showed a significant difference across time points (p = 0.000), indicating that the educational intervention had a short-term impact. However, the decline in scores suggests limited long-term retention, likely due to the absence of follow-up measures and restricted access to continuous information. These findings highlight the importance of sustained educational reinforcement and accessible communication channels for health interventions in rural populations.